Two analyses of Indian foodgrain production and consumption data - Sarma, J. S.; Roy, Shyamal; George, P. S.; International Food Policy Research Institute (Washington, D.C. : International Food Policy Research Institute, 1979)
This book is on Indian's food grain production, consumption and imports.
Includes bibliographies.
oo 15/04/2019
Loans
Keywords: Grain trade; Food consumption; Food supply